Factors Affecting the Perception and Practice of Iranian Nomadic and Semi-Nomadic Pastoralists in Regard to Biosecurity Practices in Sheep and Goat Farms: A Cross-Sectional and Prospective Study - Hatami Z; Laven RA; Jafari-Gh S; Moazez-Lesko M; Soleimani P; Jafari-Gh A; Eila N; Yadi J; Sinafar M (MDPI (Basel, Switzerland), 2022)
Preventing the spread of diseases between and within farms (biosecurity) is essential for minimizing animal mortality and morbidity, as well as for reducing the risk of spread of zoonotic diseases. These effects are even greater in countries such as Iran, which have to deal with multiple ongoing epidemics of infectious disease. However, there is currently no published information about biosecurity practices on sheep and goat farms in Iran in published research. The aim of this study was to collect such information and to identify some of the factors affecting biosecurity practices. Data were gathered using a checklist and in-depth interviews with 99 nomadic and semi-nomadic pastoralists. Regression analysis was used to identify the relationships between the collected variables and the biosecurity scores. The results showed that neither within- nor between-farm disease prevention measures were appropriately applied on most farms (median total score of total biosecurity was 37.3/90; Q1 = 29.0 and Q3 = 44.7). Almost all the farmers reported slaughtering animals on farms and nobody properly disposed of the bodies of the dead animals. Additionally, the majority of the participants did not disinfect the umbilical cords of newborns. Of the collected variables, the annual mortality rate was associated with most within-farm biosecurity practices. The increase in annual mortality rates was associated with the regular cleaning of troughs (p = 0.03), preventing feed and water from being contaminated by urine and feces (p = 0.02), providing a clean and dry place for animals to rest (p = 0.05) and disinfecting the navel cord (p = 0.03). The results of this survey suggest that there is a clear need for extension programs to enhance Iranian and sheep and goat farmers’ perceptions and practices regarding biosecurity measures.
Keywords: small ruminants; animal health; preventive measures; disease prevention; animal welfare